PERBANDINGAN ANGKA KEBERHASILAN PEMASANGAN LARYNGEAL MASK AIRWAY (LMA) PROSEAL PADA USAHA PERTAMA ANTARA TEKNIK CUFF TIDAK DIKEMBANGKAN DENGAN CUFF DIKEMBANGKAN SEBAGIAN - KUSUMAWARDANI, DWI INDRIATI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Background: The first attempt success rate of Laryngeal Mask Airway (LMA) Proseal insertion is still low (82%). Various changes technique of LMA Proseal insertion are done to increase the first attempt insertion success rate. Cuff partially inflated technique (half of the recommended volume) causes the anterior surface of LMA becomes soft so LMA insertion through the curves of the posterior pharynx more easily. The advantages of this technique is practical, easy to do, does not require an assistant and does not need additional tools. This study aimed to test the hypothesis that the success rate of LMA Proseal in the first attempt with a cuff partially inflated higher than the cuff fully deflated. Methods: This study was conducted with randomized controlled trials, parallel design involving 84 ASA I or II patients undergoing general anesthesia. Patient was randomly allocated into two groups of 42 patients included in the LMA cuff was fully deflated (group T) and 42 patients in the group partially inflated of the LMA cuff (group D). The time required for successful insertion of the LMA in the first attempt was being investigated Results: The first attempt success rate of LMA Proseal insertion is defined as a successfull LMA Proseal’s insertion to maintain airway patency, with no repositioning and effective ventilation with insertion time less than 12 seconds. First attempt success rate were significantly (p<0,05) higher in cuff partially inflated technique (73,8%) than cuff fully deflated (47,6%). The speed of insertion was significantly faster with cuff partially inflated technique 9,72 ± 4,94 seconds than cuff fully deflated 12,74 ± 7,48 seconds. Conclusion: Cuff partially inflated technique is associated with easiness of LMA Proseal insertion on a first attempt, compared with cuff fully deflated.